2016
DOI: 10.1002/chem.201600590
|View full text |Cite
|
Sign up to set email alerts
|

New Red‐Emitting Tetrazine‐Phenoxazine Fluorogenic Labels for Live‐Cell Intracellular Bioorthogonal Labeling Schemes

Abstract: The synthesis of a set of tetrazine-bearing fluorogenic dyes suitable for intracellular labeling of proteins in live cells is presented. The red excitability and emission properties ensure minimal autofluorescence, while through-bond energy-transfer-based fluorogenicity reduces nonspecific background fluorescence of unreacted dyes. The tetrazine motif efficiently quenches fluorescence of the phenoxazine core, which can be selectively turned on chemically upon bioorthogonal inverse-electron-demand Diels-Alder r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
45
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 56 publications
0
45
0
1
Order By: Relevance
“…Very recently, Lemke, Kele and coworkers reported the genetic incorporation of dioxo-TCO 2 and demonstrated that the lower lipophilicity of this molecule resulted in improved washout times during imaging experiments. In Diels–Alder reactions with tetrazines, the reaction rate with 2 is similar to that with the parent TCO 36,40…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Very recently, Lemke, Kele and coworkers reported the genetic incorporation of dioxo-TCO 2 and demonstrated that the lower lipophilicity of this molecule resulted in improved washout times during imaging experiments. In Diels–Alder reactions with tetrazines, the reaction rate with 2 is similar to that with the parent TCO 36,40…”
Section: Introductionmentioning
confidence: 85%
“…In Diels-Alder reactions with tetrazines, the reaction rate with 2 is similar to that with the parent TCO. 36,40 …”
Section: Introductionmentioning
confidence: 99%
“…Tetrazine-based fluorogenic probes 1620 are particularly interesting as the tetrazine moiety within these molecules serves as reactive group and fluorescence quencher at the same time. Hence, conversion of the tetrazine in DA inv results in the loss of its quenching properties.…”
Section: Introductionmentioning
confidence: 99%
“…Such an approach is used routinely in the labeling schemes of various proteins, in cellulo or in vivo [6][7][8][10][11][12].In terms of reaction kinetics, biocompatibility, synthetic accessibility, and compatibility with GCE, strain promoted azide-alkyne cycloaddition (SPAAC) of azides and strained alkynes [13] and the inverse electron demand Diels-Alder (IEDDA) reaction of tetrazines and strained alkenes/alkynes [14] are the most robust bioorthogonal reactions. Besides, as we and others have recently demonstrated, functional groups of the SPAAC and IEDDA reactions, i.e., the azide and the tetrazine moieties, are able to modulate (i.e., quench) fluorescence by various mechanisms (e.g., energy transfer [15][16][17], rotation-induced relaxation [18,19], or photoinduced electron transfer [20]). Upon transformation of the quenching bioorthogonal unit in a specific ligation reaction, the fluorescence reinstates (Scheme 1).…”
mentioning
confidence: 88%